DIVERSIFIKASI PRODUK AYAM KAMPUNG DAN PENDAMPINGAN SERTIFIKASI HALAL PRODUK PANGAN DI DESA RANOOHA RAYA, MORAMO UTARA - Libriani, Restu; Fitrianingsih, Fitrianingsih; Sulfitrana, Andini; Toba, Racmita Dewi S.; Rejeki, Sri (HIRONO : Jurnal Pengabdian Masyarakat, 2024)
Article 4 of Law No. 33 of 2014 states that every product that enters, circulates, and is traded in Indonesia must be certified halal. The obligation for halal certification for products entering, circulating, and being traded in the Indonesian territory will be enforced starting October 17, 2024. Diversification of native chicken products into various products is highly feasible to increase product variants, thereby enhancing their marketability and bringing financial benefits to farmers. The community service activities carried out aim to (1) motivate native chicken farmers to diversify their products, (2) optimize the productivity of native chicken farmers, and (3) socialize and assist in the application for halal certification of food products. The methods used are counseling and Q&A sessions. The results of these activities showed a high level of community enthusiasm, as evidenced by the punctual attendance of community members, with an attendance rate reaching 90%, and their participation in providing tools and materials to support the activities. Based on the evaluation results, it was found that 89% of the participants understood how to process chicken meat into meatballs, shredded chicken, and floss, and 97% of the participants liked the results.